Fibulin-1 functions as a prognostic factor in lung adenocarcinoma. (16th July 2015) - Cui, Yuan; Liu, Jian; Yin, Hai-Bing; Liu, Yi-Fei; Liu, Jun-Hua
Abstract : Objective: Fibulin-1 is a member of the fibulin gene family, characterized by tandem arrays of epidermal growth factor-like domains and a C-terminal fibulin-type module. Fibulin-1 plays important roles in a range of cellular functions including morphology, growth, adhesion and mobility. It acts as a tumor suppressor gene in cutaneous melanoma, prostate cancer and gastric cancer . However, whether fibulin-1 also acts as a tumor suppressor gene in lung adenocarcinoma remains unknown. We also determined the association of fibulin-1 expression with various clinical and pathological parameters, which would show its potential role in clinical prognosis. Methods: We investigated and followed up 140 lung adenocarcinoma patients who underwent lung resection without pre- and post-operative systemic chemotherapy at the Affiliated Hospital of Nantong University from 2009 to 2013. Western blot assay and immunohistochemistry were used to evaluate the expression of fibulin-1 in lung adenocarcinoma tissues. We then analyzed the correlations between fibulin-1 expression and clinicopathological variables as well as the patients' overall survival rate. Results: Both western blot assay and immunohistochemistry demonstrated that the level of fibulin-1 was downregulated in human lung adenocarcinoma tissues compared with that of normal lung tissues. Fibulin-1 expression significantly correlated with histological differentiation ( P = 0.046), clinical stage ( P < 0.01), lymph node status ( P = 0.038) and expression of Ki-67 ( P = 0.013). More importantly, multivariate analysis revealed that fibulin-1 was an independent prognostic marker for lung adenocarcinoma, and high expression of fibulin-1 was significantly associated with better prognosis of lung adenocarcinoma patients. Conclusions: The results supported our hypothesis that fibulin-1 can act as a prognostic factor in lung adenocarcinoma progression.